Hubungan Antara Degradasi Mangrove Segara Anakan dan Penurunan Hasil Tangkapan Kepiting Bakau (Scylla sp.) di Kabupaten Cilacap, Provinsi Jawa Tengah - Ismail Ismail; Sulistiono Sulistiono; Sigid Hariyadi; Hawis Madduppa (Jurnal Ilmu Pertanian Indonesia, 2019)
The area of mangrove Segara Anakan has a high economic value so that there is a high interest to various land uses in this area. This condition leads to the change in ecological function of the mangrove which has impacts on the decreased production of mangrove crabs. This study was desighed to analyze the areas of catching crabs related to mangrove ecosystem. This study was conducted for six months in the 3 mudcrab catching areas (Western Area, Central Area, and Eastern Area). The analysis used in this study was a one way ANOVA statistic for the crabs catching in these 3 catching areas, and a simple linear regression to analyxe the correlation betwen annual crab production and mangrove area. The results showsed that mud crabs catchings in the 3 areas is 5861.7; 6072.87; dan 7689.4 kg were significantly different (P<0.05) and the linear regression between the area of mangrove in Segara Anakan and crab’s production of the Cilacap Regency was Y= 14.951X-88357 with R2 = 0.54. These results described that the number of crabs catching was influenced by the condition of mangrove in the 3 catching areas while the regressionb analysis showed that the decreased mud crab’s production in Cilacap Regency was correlated to the decrease in the area of mangrove Segara Anakan.